Time reduction in a forced-convection thermal process using simplified transient analysis - Sobrinho, P. M.; Magalhaes, P.; Carvalho, J. A. (Elsevier B.V., 2001)
This study investigates the utilisation of a simplified model in the transient analysis of a thermal cooling process. In such process the external thermal resistance between the surface and the surroundings is high compared to the system internal thermal resistance, so that the first controls the heat transfer process. In this case the Biot number is lower than 0.1. Aluminium reels were utilised, which, with proper internal instrumentation, furnished experimental results for the thermal cooling process. Based on experimental data, a simplified model for the determination of the process film coefficient was used. Subsequently, experimental and theoretical results were compared. The change of the airflow direction was also investigated for the cooling process, aiming at process time optimisation. (C) 2001 Elsevier B.V. Ltd.